Analisis Penyelesaian Kredit Bermasalah Pada Perumda. Bpr Bank Gresik - Viqka Anggraeni; Anita Handayani (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study is to broaden the understanding of lending, especially from the point of view of the problems of the loan settlement procedure carried out by PERUMDA BPR Bank Gresik. When analyzing the data, the authors use the method of qualitative analysis, systematically separating data from the obtained facts, which are then linked to the bad debt settlement procedure at PERUMDA BPR Bank Gresik. The results of this study point to the causes of troubled debts caused by the internal factors of the bank and the factors of influence of the external (client). If the bank is less meticulous when analyzing the possibility of obtaining a loan. If the client does not deserve a loan, but due to a careless or incorrect assessment of the client deserves a loan. and from an ektern (client) that the availability of credit to the consumer due to the economic downturn, which the buyer received, was used to develop the business, and the business was terminated. Bad debt recovery is performed PERUMDABPR Bank Gresik refers to the process of rescheduling or rescheduling, restructuring, or restructuring loans in the form of restructuring conditions and back readjustments.